Representasi Nilai-Nilai Islam dalam Podcast Login (Analisis Isi Model Philipp Mayring) - Shaliha, Faradiba; Soiman; Soiman, Soiman (Analisis: Jurnal Studi Keislaman, 2025)
The increasing use of digital media as a means of preaching is the impact of technological developments that encourage preachers to utilize various digital platforms to facilitate preaching activities. One of the popular platforms used is YouTube, which provides various preaching content. One of the preaching contents on this platform is the "Login" podcast which is presented in video format. This study aims to identify and describe the Islamic values ​​represented by Habib Ja'far through the "Login" podcast. This study uses a descriptive qualitative approach with content analysis techniques developed by Philipp Mayring. Data were collected through observation, documentation, and literature studies. The results of this study found various preaching messages conveyed by Habib Ja'far in the 18th episode of the "Login" podcast. The researcher found 12 Islamic values, consisting of 2 values ​​in the Akidah category, 5 values ​​in the Sharia category, and 5 values ​​in the Morals category. Based on content analysis using the Philipp Mayring Model, this podcast successfully presents Islamic teachings that are very relevant to the modern social context, especially related to gender equality, tolerance, and justice. One of the new findings is the raising of the issue of equality in marriage, where husbands and wives are invited to make decisions together and emphasize the importance of respecting the rights and dignity of women in Islam, which is often neglected in patriarchal interpretations.